Proposed new interior design of Pak Ngah Production Academy for Pak Ngah Production Sdn. Bhd. at Lot 254 Jalan Ampang, 50450, Ampang, Kuala Lumpur / Muadzin Ishak - Ishak, Muadzin (Faculty of Architecture, Planning and Surveying, 2011)
The final project for the student of Diploma in Interior Architecture is a manifestation towards the student’s knowledge about the whole aspect on interior design that had been learnt from basic to the final presentation on the proposed design. The project that had been chosen for the final project is to Proposed New Interior Design of Pak Ngah Production Academy for Pak Ngah Production Sdn. Bhd. at Lot 254, Jalan Ampang, 50450 Ampang, Kuala Lumpur, Selangor Darul Ehsan. Pak Ngah Production Sdn. Bhd was well known recording studio since opened in 1995 which is includes arrangers, composers, scriptwriters, producers, directors, actors, dancers etc. This proposed academy is to attract children and teenagers especially to learn and know about our Malay culture and traditional performances including stage performances, traditional dances and music. The target market for the users of this studio academy are children from age 4 until adult that not know basic about Malay dances, music and stage performances. Concept and image that had been chosen not only must be suitable with the clients as both of it would reflect the client itself. So, the chosen design style for Pak Ngah Production Academy is based on modern contemporary design, but still apply the traditional spirit and at the same time would attract the customers with different image that they would only get in Pak Ngah Production Academy only. Before getting the design that is suitable with the client’s needs, some data analysis should be done such as the types of customers to attend the session, types of services offered, Pak Ngah Production product, spaces to be concluded in the proposed area, operation time and information about other studio academy that use the same system in management, as the proposed studio academy. The study was performed including site selection studies, interview studies, observation studies,case studies and research with a questionnaire. Research and data collection process will be analyzed and applied in the design process to design a comfortable and attractive addition to creating a new image with a touch of style and image of its own.